1997
DOI: 10.1159/000111245
|View full text |Cite
|
Sign up to set email alerts
|

The Expression of Messenger RNAs Coding for Growth Factors, Their Receptors, and eph-Class Receptor Tyrosine Kinases in Normal and Ototoxically Damaged Chick Cochleae

Abstract: Messenger RNAs coding for growth factors and receptor tyrosine kinases were measured by quantitative competitive and by semi-quantitative reverse-transcription polymerase chain reaction in whole and dissected chick inner ears. The fibroblast growth factor (FGF) receptor 1 chick embryonic kinase (CEK) 1 was expressed in all structures examined (otocyst, hatchling whole cochlea, cochlear nerve ganglion, and cochlear and vestibular sensory epithelia),although slightly more heavily in the otocyst. The related fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
51
0
1

Year Published

1999
1999
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 27 publications
0
51
0
1
Order By: Relevance
“…Progenitors also continue to divide in serumfree medium, indicating that mitotic substances are intrinsic to the inner ear organs (52,53). A number of fibroblast growth factors that bind and activate tyrosine kinase receptors are known to be present in inner ear organs (54,55). The expression levels of many of these factors are changed after HC damage, although their mitogenic properties have not yet been determined.…”
Section: Mitotic Hc Regenerationmentioning
confidence: 99%
“…Progenitors also continue to divide in serumfree medium, indicating that mitotic substances are intrinsic to the inner ear organs (52,53). A number of fibroblast growth factors that bind and activate tyrosine kinase receptors are known to be present in inner ear organs (54,55). The expression levels of many of these factors are changed after HC damage, although their mitogenic properties have not yet been determined.…”
Section: Mitotic Hc Regenerationmentioning
confidence: 99%
“…It is generally believed that molecules involved in axon guidance during embryonic development could be reused in the adult after lesioning axon tracts to re-establish the functional integrity of neuronal circuits (Aubert et al 1995). Up-regulation of Eph receptor expression is observed following injury to the adult spinal cord (Miranda et al 1999), hippocampus (Moreno-Flores andWandosell 1999), and cochlear nucleus (Pickles and van Heumen 1997). In lower vertebrates, such as fish and amphibians, retinal ganglion cells (RGCs) are newly formed throughout life, and retinal axons continuously regrow into the tectum.…”
Section: Neuroregenerationmentioning
confidence: 99%
“…These growth factors bind to and activate tyrosine kinase receptors, many of which also are expressed in the avian inner ear. PCR studies have shown that mRNAs for FGF receptor (FGFR)-1, epidermal growth factor receptor (erbB1), and IGF receptor-1 are present in the cochlear duct (61) and, more specifically, in the sensory epithelium (59). Further, in situ hybridization reveals abundant message for FGFR-3 in the supporting cells (unpublished observation).…”
Section: Avian Hair Cell Progenitors: Identity and Behaviormentioning
confidence: 89%
“…Further, in situ hybridization reveals abundant message for FGFR-3 in the supporting cells (unpublished observation). After hair cell damage, there are detectable changes in the levels of transcripts for FGF-1, IGF receptor-1, FGFR-1, and FGFR-3, but not for IGF-1, FGF-2, or ErbB1 (59,61). At the protein level, FGFR-1 is present in hair cells in control tissue, and then it becomes elevated in supporting cells after hair cell damage (59,61).…”
Section: Avian Hair Cell Progenitors: Identity and Behaviormentioning
confidence: 99%
See 1 more Smart Citation